Memória e resistência: os professores no contexto da ditadura civil-militar (1964-1985) - Hebling, Milene Cristina (2013)
This is a study about the resistance of teachers of first and second degree to brazilian military regime. We try to identify which resistance practices were developed by these teachers and understand if they were organized in the individual sphere, as isolated actions of some teachers, or collectively, as an organization of professional category. Beyond that, we are also interested in investigating if this resistance had used the teacher profession as a support, being performed through pedagogical practices, or if it occurred outside the school environment, not presenting a relation, therefore, with the teaching activity. To treat our research object, we used two methodological strategies, which are oral history and documental research. For the realization of oral history, were previously selected eleven teachers who had lectured in primary or secondary school during the civil-military dictatorship. Of this total, six were located and four agreed to participated of the research. We conducted semi-structured interviews, using a predefined questionnaire as a guide, in order to know memories of the participants about the researched topic. The documental research was realized in the collection of the Departamento Estadual de Ordem Política e Social (DEOPS/SP), in order to find documents produced by this politics police organ about the studied teachers. We attribute great relevance to the oral sources obtained, due the possibility they represent of understanding our object of study from the point of view of the involved, i.e., the teachers. This research did not seek to be generalizing, since we do not work with samples, but with specific cases. In the analysis of collected sources, were constructed thematic axes which address different resistance practices developed by the focused teachers and the repression suffered by their actions. These axes are: "Presentation of teachers"; "resistance through the profession: possibilities and limits"; "resistance out of school" and "repression." As result, it can be seen that the participants built, through various practices, resistance to the military regime. Moreover, the opposition performed by these teachers was bounded by the characteristics of the opposition movement of society in general, i.e., the resistance developed by them was integrated into the social and political context in which the country was in each period of civil-military dictatorship.